Fluorinated Alkyl Chains Terminated Polar Glycol Ether Side Chain for N‐Type Organic Thermoelectrics with Enhanced Performance and Air Stability - Gang Ye; Yazhuo Kuang; Mingyu Ma; Xiantao Peng; Jian Liu (Advanced Science, 2025)
Abstract N‐type organic thermoelectric materials with excellent device performance and air stability are critically important for practical applications in organic thermoelectric devices. However, the design and synthesis of air‐stable n‐type conductive materials with high electrical conductivities remain a significant challenge. In this paper, a new strategy is reported to enhance the thermoelectric performance and air stability of naphthalenediimide (NDI)‐dialkoxybithiazole‐based conjugated polymers by introducing fluorinated alkyl chains terminated polar glycol ether side chains into the NDI unit. After molecular doping with 4‐(2,3‐dihydro‐1,3‐dimethyl‐1H‐benzoimidazol‐2‐yl) phenyl)‐N, N‐dimethylbenzenamine (N‐DMBI), the doped films of the fluorinated alkyl side‐chain modified conjugated polymer exhibit higher electrical conductivity, thus resulting in a greater power factor; and better air stability compared to those of the unmodified polymer with the same conjugated backbone. The work provides insights into material design for the future development of air‐stable n‐type organic thermoelectrics.